2020
DOI: 10.1001/jamaoncol.2019.6584
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Safety and Efficacy of Combined Trabectedin and Low-Dose Radiotherapy for Patients With Metastatic Soft-Tissue Sarcomas

Abstract: IMPORTANCEActive therapeutic combinations, such as trabectedin and radiotherapy, offer potentially higher dimensional response in second-line treatment of advanced soft-tissue sarcomas. Dimensional response can be relevant both for symptom relief and for survival.OBJECTIVE To assess the combined use of trabectedin and radiotherapy in treating patients with progressing metastatic soft-tissue sarcomas.DESIGN, SETTING, AND PARTICIPANTS Phase 1 of this nonrandomized clinical trial followed the classic 3 + 3 design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…Here, we report on a retrospective series of 40 patients with advanced soft-tissue sarcoma treated, in real-life, with the combination of trabectedin plus radiotherapy in a sarcoma reference center. The results in this series are in line with the previous published study considering the median PFS [ 15 ], and clearly exceed those expected for trabectedin alone, or other approved second line drugs for sarcoma [ 6 , 7 , 8 ]. It is important to highlight that these results were obtained with trabectedin and external beam conventional RT in a population with bulky (median size of the irradiated lesion exceeded 5 cm), pretreated, and symptomatic disease.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Here, we report on a retrospective series of 40 patients with advanced soft-tissue sarcoma treated, in real-life, with the combination of trabectedin plus radiotherapy in a sarcoma reference center. The results in this series are in line with the previous published study considering the median PFS [ 15 ], and clearly exceed those expected for trabectedin alone, or other approved second line drugs for sarcoma [ 6 , 7 , 8 ]. It is important to highlight that these results were obtained with trabectedin and external beam conventional RT in a population with bulky (median size of the irradiated lesion exceeded 5 cm), pretreated, and symptomatic disease.…”
Section: Discussionsupporting
confidence: 90%
“…A potential explanation of the lower response rate observed in the present series with respect to the clinical trial is the lower adherence to the concomitant schedule of therapy. In the previous clinical trial [ 15 ], all patients started RT immediately after the complexion of the first cycle of trabectedin. In this real-life series, a third of the patients started RT more than 24 h after trabectedin, and this delay in the initiation of RT could have impacted on the activity of the combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have reported the effects of these drugs for controlling recurrent and bleeding local lesions such as those observed in our patient. Martin-Broto et al 9 reported the safety and efficacy of combined low-dose radiotherapy and trabectedin for patients with metastatic soft tissue sarcomas. In their study, combined radiotherapy at a dose of 30 Gy and trabectedin was effective for patients with metastatic soft-tissue sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Our experience, however, suggests that investigation of MSI-status in these patients may be worthwhile in patient-speci c treatment choice with minimal toxicity, either as monomodality treatment (for example in the case of RT with moderate doses to large volumes encompassing all macroscopic disease) or -even more likely to result in local and systemic response -as a combination of RT and IT [23], which may result in a dramatic bene t for these patients. The concept of applying moderate RT doses to macroscopic disease in combination with newer sensitizing systemic agents is currently investigated in various settings, with rst promising results, for example for the combination of palliative dose RT and Trabectidin in patients with metastatic soft tissue sarcoma, having been reported recently [24].…”
Section: Discussionmentioning
confidence: 99%